Cholinesterase activity on Echinogammarus meridionalis (Pinkster) and Atyaephyra desmarestii (Millet): characterisation and in vivo effects of copper and zinc - Quintaneiro, C.
Metals are released into freshwater ecosystems from natural and anthropogenic sources, compromising their structural and functional equilibrium. As early warning tools, cholinesterases (ChEs) are usually used to assess the effects of organophosphate and carbamate pesticides, but are also known to be inhibited by metals. The objectives of this work were to characterise the activity of ChE present in the amphipod Echinogammarus meridionalis and the shrimp Atyaephyra desmarestii and to evaluate the in vivo effects of the metals copper and zinc in their ChE activity. To achieve this, firstly the activity of ChE forms were characterised using different in vitro assays with substrates and selective inhibitors. Then, the in vivo effects of 48 h exposures to increasing concentrations of copper and zinc on ChE activity were determined. The ChE form present in both species was acetylcholinesterase (AChE) since both revealed preference for the acetylthiocholine iodide substrate, total inhibition with eserine, the inhibitor of ChEs, and with 1,5-bis(4-allyldimethylammoniumphenyl)-pentan-3-one dibromide, the specific inhibitor of AChE, and presented insensitivity to iso-OMPA, a specific inhibitor of butyrylcholinesterase. The activity of ChEs was inhibited by zinc exposures in the amphipod species, but was not affected by copper. Exposure to copper and zinc did not affect ChEs activity in the shrimp at the concentrations tested. This work is a relevant contribution as foundation for the use of AChE in freshwater crustaceans in further studies including biomonitoring campaigns in different contamination scenarios.